Impact of Visiting the Jurnal Pendidikan IPA Indonesia Website to the Author's Knowledge - Parmin, Parmin; Savitri, Erna Noor; Amalia, Andin Vita; Khusniati, Miranita; Febriyana, Anggie (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
The research objective is to reveal the knowledge of people who have visited the Jurnal Pendidikan IPA Indonesia (JPII) website about articles with international standards. The instruments used were questionnaires and interviews which were conducted a feasibility test before being used. The strategy employed was sequential explanatory by collecting and analyzing quantitative data followed by qualitative data. The articles of the participants were still unassigned and submitted from July to August 2020. The number of participants was 85 consisting of 78 lecturers, 4 students, and 3 teachers. The research results from questionnaire analysis were; the participants’ intention of visiting the JPII website as 53% to cite articles, the benefit that obtained was 69% getting references, the most interesting part of 62% was the results and discussion, the substance primacy of 35% was in the discussion section, and participants find it easiest to find novelties in the discussion section of 53%. The interview results with 79 participants (93%) stated that they had gained knowledge about international standard articles that had these characteristics; interesting topics, strong gap analysis, methods that are detailed and have novelty, and discussion that has a clear novelty.